Solutions to Problems in
Modern Quantum Mechanics, 2nd edition
by J.J. Sakurai and Jim J. Napolitano
C ONTENTS
1 Fundamental Concepts
1 FUNDAMENTAL CONCEPTS
1 F UNDAMENTAL C ONCEPTS
1. First, note that [, ] and {, } refers to the commutator and anticommutators of the operators, respectively.
Hence, using the property: [A, BC ] = B [A,C ] + [A, B ]C and [AB,C ] = A[B,C ] + [A,C ]B :
[AB,C D] = AC [B, D] + A[B,C ]D +C [A, D]B + [A,C ]DB
= AC (B D DB ) + A(BC C B )D +C (AD D A)B + (AC C A)DB
= AC (B D DB ) + A(C B + BC )D +C (AD D A)B + (C A + AC )DB
= AC {D, B } + A{C , B }D C {D, A}B + {C , A}DB
2.
3
X
a i i
i =1
where ~
I is the identity matrix. Since t r (i ) = 0 for i = 1, 2, 3, we have:
0
= 2a 0
a0
a0
t r (X ) = t r
0
Also, we have:
t r (k X ) = t r a 0 k +
3
X
a x k x
x=1
3
X
= tr
a x i kx y y + kx I
x=1
= t r (a k I )
= 2a k
since a b = i abc c + ab I in general and t r (a x y ) = 0 for any x, y = 1, 2, 3.
b) We have the matrix elements:
a0 + a3
X=
a1 + i a2
a1 i a2
a0 a3
Hence we have:
1
a 0 = (X 11 + X 22 )
2
1
a 2 = (X 21 X 12 )
2i
1
a 1 = (X 12 + X 21 )
2
1
a 3 = (X 11 X 22)
2
a3
a1 + i a2
a1 i a2
a 3
= a 32 (a 1 i a 2 )(a 1 + i a 2 )
= a 12 a 22 a 32
= ~
a 2
1 FUNDAMENTAL CONCEPTS
X 1 i z k
i z
=
exp
2
2
k=0 k!
k
k1
k
X (1) 2
X (1) 2
=I
z
i
2
k!
2
k=even k!
k=od d
= I cos
i z sin
2
2
0
cos 2 i sin 2
=
0
cos 2 i sin 2
i
!
e 2
0
=
i
0
e 2
0
i
e 2
a3 e
i
a1 i a2 e 2
a 3
0
i !
i
(a 1 i a 2 )e 2 e 2
a3
a1 + i a2
i
2
i
(a 1 + i a 2 )e 2
a 3 e 2
(a 1 i a 2 )e i
a 3
a3
=
(a 1 + i a 2 )e i
d et (~
~
a 0 ) = a 12 a 22 a 32 = ~
a 2
= d et (~
~
a)
Also, noting that:
a 30
0
a 1 + i a 20
a 10 i a 20
a 30
a3
(a 1 + i a 2 )e i
(a 1 i a 2 )e i
a 3
Therefore, we have:
1
(a 1 i a 2 )e i + (a 1 + i a 2 )e i
2
= a 1 cos + a 2 sin
1
a 20 =
(a 1 + i a 2 )e i (a 1 i a 2 )e i
2i
= a 2 cos a 1 sin
a 10 =
a 30 = a 3
This is a counterclockwise rotation about the zaxis of angle .
i
2
0
e
~
~
a0 =
i
2
4.
1 FUNDAMENTAL CONCEPTS
a 0  X Y a 0
a0
XX
a0
a 0  X a 00 a 00  Y a 0
a 00
XX
a 00  Y a 0 a 0  X a 00
a 0 a 00
a 00  Y X a 00
a 00
= t r (Y X )
b) Looking at the matrix elements:
(X Y ) a 0 a 00 = a 0  X Y a 00 = X a 0  Y a 00
= Y X a 0 a 00
for any a 0 and a 00 . Therefore, we have (X Y ) = Y X .
c) Suppose that A has eigenvalues:
A a i = a i a i
Taylor expanding the exponential, we have:
1
X
k
i f (A) a 0
k=0 k!
X 1
X
(i f (A))k a i a i a 0
=
k!
k=0 i
X 1
X
=
(i f (a i ))k a i a i a 0
k!
k=0 i
X
= exp[i f (a i )] a i a i a 0
exp[i f (A)] a 0 =
exp[i f (a i )] a i a i 
a 0 (x 0 )a 0 (x 00 ) =
a 0 x 0 x 00 a 0
a0
x 00 a 0 a 0 x 0
a0
= x 00 x 0
5.
1 FUNDAMENTAL CONCEPTS
1 1 1
  = p
2 0 0
6. Suppose that:
A i = i i
A  j = j  j
Then, we have:
A(i +  j ) = i i + j  j
Thus, we need the states to be degenerate: i = j for i +  j to also be an eigenket for A:
A(i +  j ) = i (i +  j )
7.
(A a 0 )  =
XY
a0
a 00  (A a 0 ) a 00
a 00 a 0
XY
a 00
a 00  (a 00 a 0 ) a 00
a0
=0
since for each a 00
Y
(a 00 a 0 ) = 0
a0
a
)
(a
00
0
000
00
0
a 6=a
a a 6=a
X Y (a 000 a 00 ) 000
a  a 000
0 a 00 )
(a
000
00
0
a a 6=a
X
= a 000 ,a 0 a 000  a 000
a 000
= a 0  a 0
Hence it projects the a 0 component of an arbitrary ket.
1 FUNDAMENTAL CONCEPTS
c) For A = S z , and a ket space spanned by {+ , }, we can construct an arbitrary ket :
 = a + + + a 
for some complex numbers a + and a .
Then, operating on it by the first operator:
2
(S z + )(S z )s  = (S 2z ) 
2
2
4
2
= (S 2z )(a + + + a )
4
2
2
2
= a + + + a  a + + + a 
4
4
4
4
=0
Operating on it by the second operator: first, for a 0 = /2,
S z + 2
+ 2
 =
Sz +
(a + + + a )
1
(a + +)
= a + +
and the completely analogous process leads to the a 0 = /2 case, in which it results in a .
8. First, the commutator is trivially zero if i = j . For i 6= j :
i 2
(+ +   ( + + +  ))
4
i 2
=
(2 + + 2  )
4
= i (+ +  )
2
= i S z
[S x , S y ] =
2
( +  +  + (+   +))
4
i
= i ( +  +  +)
2
[S x , S z ] =
= i S y
i 2
(+  +  + ( +   +))
4
= i (+  +  +)
2
= i S x
[S y , S z ] =
Hence, we have: [S i , S j ] = i i j k S k .
Next, for i 6= j , the anticommutators evaluate:
{S x , S y } = {S x , S z } = {S y , S z } = 0
1 FUNDAMENTAL CONCEPTS
{S i , S j } =
2
~
I i j
2

2
i

S y + =
2
+
2
i
S y  = +
2
S x + =
S x  =
Sx
cos sin
i
= cos sin (a +  + a +) + sin sin (a +  a +)
2
2
+ cos (a + + a )
2
= a + cos + a e i sin + +
a + e i sin a cos 
2
2
and the right side of the equation is:
(a + + + a )
2
a+
a+
=
a
a
1 FUNDAMENTAL CONCEPTS
e i sin
a
1 cos
sin2
+
1
a 2 = 1
(1 cos )2
1
a 2 = (1 cos ) = sin2
2
2
1
a + 2 = (1 + cos ) = cos2
2
2
Therefore, we have:
2
i
a = sin e
2
a + = cos
=
sin e i ()
2 1 cos
2
1
cos
e i () =
cot
sin
2
1 cos sin
=
=1
sin 1 cos
cos
Thus, we need = .
Therefore, the eigenket is:
+ = cos
~
S n;
+ + sin e i 
2
2
1 1
H =a
1 1
1 1 a1
0 a1
a
=a
1 1 a 2
a2
1 FUNDAMENTAL CONCEPTS
And hence:
p
a 1 + a 2 = 2a 1
p
a 1 a 2 = 2a 2
In other words:
p
a 2 = ( 2 1)a 1
Hence:
a 0 = C
1
p
21
p
p
a 0 a 0 = C 2 1 + ( 2 1)2 = C 2 4 2 2 = 1
C=q
1
p
2(2 2)
p
1 + ( 2 1) 2
p
2(2 2)
p
1
1 ( 2 + 1) 2
a 20 = q
p
2(2 + 2)
a 10 =
p
2a
p
a 10 = 2a
H11 + H22
H11 H22
(1 1 2 2) + H12 (1 2 + 2 1)
(1 1 + 2 2) +
2
2
2
(1 2 + 2 1) S x